Pengaruh Kompetensi, Etika Kerja dan Teamwork Terhadap Kinerja Karyawan Pada PT. BPR Tish Batubulan - Putra, I Wayan; Putu Kawiana, I Gede; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Employee performance improvement is one of every company goals so that the company can maximize its profit. One of the effort that PT. BPR Tish do to improving employee work is paying attention to some factors including competence, work ethic and teamwork. This studyâ€™s aim to determining how competence, work ethic and teamwork can influence the employee performance in PT. BPR Tish Batubulan, Gianyar.  This study used 42 employees of PT. BPR Tish as samples and analyzed using regression analysis. The result shows that: (1) competence has positive and significant influence on employee performance, (2) work ethic has positive and significant influence on employee performance, (3) teamwork has positive and significant influence on employee performance, (4) competence, work ethic and teamwork have positive and significant influence simultaneously on employee performance at PT. BPR Tish Batubulan. Variation of competence, work ethic and teamwork variabels were able to influence employee performance variabel by 79,7% and up to 20,3% influenced by the other variabels that are not included in this study.